Glassy carbon electrodes modified with gelatin functionalized reduced graphene oxide nanosheet for determination of gallic acid - Chekin, F.; Bagheri, S.; Abd Hamid, S.B. (2015)
A simple approach for the preparation of gelatin functionalized reduced graphene oxide nanosheet (Gel-RGONS) by chemical reduction of graphene oxide (GO) using gelatin as both reducing agent and stabilizing agent in an aqueous solution was developed. The morphology and structure of the Gel-RGONS were examined by X-ray diffraction, transmission electron microscopy, ultraviolet-visible spectroscopy and Raman spectroscopy. Gelatin acted as a functionalizing reagent to guarantee good dispersibility and stability of the r in distilled water. Moreover, a new electrochemical sensor was developed based on Gel-RGONS modified glassy carbon electrode (Gel-RGONS/GCE). Gel-r exhibits excellent electrocatalytic activity to gallic acid (GA) oxidation. The experimental conditions such as pH, adsorption time and scan rate were optimized for the determination of GA. Under optimum conditions, the sensor responded linearly to GA in the concentration of 1.0 x 10(-6) to 1.1 x 10(-4) M with detection limit of 4.7 x 10(-7) M at 3 sigma using linear sweep voltammetry (LSV). The method has been successfully applied to the determination of GA in sample of black tea.